CAPILLARY IMBIBITION TECHNIQUES USED TO CHARACTERIZE THESTRUCTURAL CHANGES IN MICROCRYSTALLINE CELLULOSE DUE TO WET AND DRY PROCESS - P. D. Ravazzoli; M. C. Balbi; N. E. Ceschan; G. Callegari; G. Drazer (Anales (Asociación Física Argentina), 2024)
In this work we study the change on the wettability and solid properties of microcrystalline cellulose (Avicel PH101)after it was wet and dried, through drop penetration experiments in slightly compacted porous beds. We perform these experiments with water and a silicone oil, (Polidimethilsyloxane–PDMS) and we determine a dimensionless parameter that takes into account all the water penetration factors, including wettability and swelling. We consider three different scenarios, original MCC, and after one and two wetting and drying cycles. For each case we study the particle size effects by considering two subset samples SiA)25<φ<75μm and SiB)75<φ<125μm. We were able to determine, as it was expected, that PDMS penetration dynamics is not affected by the wetting–drying cycles but water is. The penetration rate goes down after cellulose was wet. Finally, we discuss how these behavior may affect the different processes where microcrystalline cellulose is used.